Measuring the effectiveness of border security between ports-of-entry - Willis, Henry H.; Predd, Joel B.; Davis, Paul K., 1943-; Brown, Wayne P.; Rand eBooks (Santa Monica, CA : RAND, 2010)
Strategic planning is necessary if the U.S. Department of Homeland Security (DHS) is to carry out its border-security missions effectively and efficiently. As part of that, DHS leadership must define concrete and sensible objectives and measures of success. These can be used to assess results along the way, to guide allocation of resources, and to inform programming and budgeting for future capabilities and functions. This report offers research and recommendations on ways to measure the overall efforts of the national border-security enterprise between ports of entry. To be meaningful, the set of measures for effectiveness of border security should be sound, reliable, useful, and general. Three DHS missions appear to currently be of special interest to DHS leadership because they are especially problematic: illegal drug control, counterterrorism, and illegal migration. The report recommends measuring performance of three fundamental functions that border-security efforts contribute to achieving national policy objectives: interdiction, deterrence, and exploiting networked intelligence. If the steps described here are taken, DHS and its components will be in a better position to discuss past performance and to provide reasoned justifications for future allocation of resources. Further, they will be able to relate their efforts to those of other agencies in pursuit of national objectives.
General missions, focus missions, and criteria for measuring effectiveness -- a conceptual model of border security as a foundation for measurement -- Contributions of border security to drug control, counterterrorism, and illegal migration -- Recommended measures for controlling drugs, immigration, and border crossing by terrorists -- Implementing steps to measure border security.
"RAND Homeland Security and Defense Center."
"This research was conducted under the auspices of the Homeland Security and Defense Center, a joint center of the RAND National Security Division and RAND Infrastructure, Safety, and Environment--Pref.
Includes bibliographical references (p. 45-48).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Department of Homeland Security -- Planning; Border patrols -- United States; Border security -- United States -- Evaluation; Ports of entry -- Security measures -- United States; Strategic planning -- United States; Electronic books